2018
DOI: 10.1177/1748895818811905
|View full text |Cite
|
Sign up to set email alerts
|

History, periodization and the character of contemporary crime control

Abstract: In recent decades, several highly influential studies have sought to articulate the changed and changing character of contemporary crime control in its historical context. While the substantive claims of these studies have attracted close scrutiny, there has been remarkably little analysis of the historiographical apparatus underpinning them. As a result, criminology has neglected to develop a valuable, critical vantage point on how crime and justice in our own times are understood. This article advances discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 68 publications
(97 reference statements)
0
26
0
Order By: Relevance
“…Third, in centering deindustrialization as simultaneously a historic event and a contemporary social force in areas suffering from its fallout, we have sought to address Rock's (2005) abiding concerns of chronocentrism in criminology. As Churchill (2019) has recently argued, criminological scholarship often relies on a periodized, epochal view of historical change—dominated by events and paradigmatic shifts—to the detriment of more fluid, path‐dependent views of incremental change. The concept of the “half‐life,” importantly, captures both views of history—drawing a connection between significant events and their ongoing legacy.…”
Section: Conclusion: From Organized Crime To Organized Harmmentioning
confidence: 99%
“…Third, in centering deindustrialization as simultaneously a historic event and a contemporary social force in areas suffering from its fallout, we have sought to address Rock's (2005) abiding concerns of chronocentrism in criminology. As Churchill (2019) has recently argued, criminological scholarship often relies on a periodized, epochal view of historical change—dominated by events and paradigmatic shifts—to the detriment of more fluid, path‐dependent views of incremental change. The concept of the “half‐life,” importantly, captures both views of history—drawing a connection between significant events and their ongoing legacy.…”
Section: Conclusion: From Organized Crime To Organized Harmmentioning
confidence: 99%
“…While penal change research often implicitly concerns stasis, presumably identified as the periods before and after a change occurs, most of the attention (and excitement) is about the change-where/when does it begin, where/when does it end? Popular representations of penal history are often periodized into distinct eras (e.g., Churchill 2019;Goodman et al 2017;Irwin 2005;Rubin 2019d) and penal change is often defined as the shift between whatever characterizes these eras as distinct: e.g., the rise of the prison, the innovation or popularity of a new type of prison, or the explosion in the frequency with which the prison is used. This model of penal change has been heavily criticized by scholars challenging the uniformity of any given era (e.g., Goodman et al 2017;Hutchinson 2006;Matthews 2005 Said in different theoretical language, punishment studies suffer from a disproportionate focus on "institutional innovation," and an insufficient attention to "institutional reproduction" (Thelen 2003).…”
Section: Change and Stasismentioning
confidence: 99%
“…From an historical perspective, the major difficulty with much work on private security is the tendencyat least in Anglophone scholarshipto discuss recent developments in terms of a paradigm shift, or an epochal break with the past. 11 The literature is peppered with phrases denoting radical change ('dramatic growth', 'fundamental shifts'), or even a new age ('latemodern', 'postmodern', 'post-Fordist', 'neoliberal'), in security provisionphrases that draw a sharp distinction between contemporary security regimes and what is presumed to have gone before. Furthermore, scholars frequently deploy terminology -the 'rise' of private security, the 'pluralisation' of policing, the 'growth' of security networks, the 'privatisation' of policing, or threats to the 'traditional domain' of the policeevocative of an imagined past before private security, plural policing or hybrid security networks, which is rarely subjected to rigorous investigation.…”
Section: A New World Of Security?mentioning
confidence: 99%